Cover Image. Issue 4 (August 2017) - Švrček, Vladimir; McDonald, Calum; Lozac'h, Mickael; Tayagaki, Takeshi; Koganezawa, Tomoyuki; Miyadera, Tetsuhiko; Mariotti, Davide; Matsubara, Koji
Abstract : The cover image, by Vladimir Švrček et al., is based on the Research Article Stable ultrathin surfactant free surface‐engineered silicon nanocrystal solar cells deposited at room temperature, DOI:10.1002/ese3.165 .